Fault tolerant control of three-level NPC grid-connected inverter based on SVPWM compensation optimization - YANG Qing; HUANG Jingtao; GUAN Haiping (电力工程技术, 2024)
To ensure the three-level neutral point clamped (NPC) grid-connected inverter in a grid-connected system continuous operation after a single-phase bridge arm short circuit or open circuit failure, an optimal compensation fault-tolerant control strategy with low common-mode voltage is proposed in this paper, which is based on space vector pulse width modulation (SVPWM). Firstly, the reference voltage vector synthesis rule is determined by analyzing the common mode voltage corresponding to the switch state of the eight-switch three-phase inverters (ESTPI), which is the topology of the three-level NPC inverter with one phase failure. Then, the mechanism of neutral point potential fluctuation is analyzed by the neutral point current change in a fundamental wave period. Further, the space vector synthesis is compensated based on this mechanism. Finally, the low-pass filter and hysteresis controller are designed to optimize vector synthesis compensation, so as to ensure the quality of grid-connected current and effectively restrain the neutral point potential offset of the DC bus. The simulation results show that the proposed fault-tolerant control strategy can realize the stable and reliable operation of the grid-connected system after single-phase bridge arm failure, and the common-mode voltage can be reduced for one-third of the period time. The quality of grid-connected current is improved significantly. The proposed controller has good control characteristics when the grid-connected current changes.